The mattering citizen: young adults with mental illness and complex needs’ experiences and perceived opportunities of social inclusion - Silje Nord-Baade; Silje Nord-Baade; Ottar Ness; Michael Rowe; Michael Rowe; Camilla Bergsve Jensen; Anne Landheim; Anne Landheim (Frontiers in Psychology)
The negative effects of social exclusion are well known, as are the effects of social inclusion on quality of life and well-being. Young adults with mental illness and complex needs are among the most marginalized people in the community. There is a pressing need to better define and promote social inclusion in mental health and substance use services, addressing both objective and subjective factors. The aim of this qualitative study was to examine the experiences and perceived opportunities of social inclusion among young adults with mental illness and complex needs. This was done to develop a comprehensive understanding of social inclusion that can be applied by providers in the fields of welfare, mental health, and substance use. Seven young adults (three males/four females, aged 22–29) were recruited through Flexible Assertive Community Treatment teams and participated in the study through qualitative semi-structured interviews. The material was analyzed employing an abductive thematic analysis. The findings show the interconnection between the elements of Citizenship and Mattering and underline the need for a framework including both the psychological and sociological perspectives. Developing the Citizenship framework and incorporating the Mattering approach is suggested as a multifaceted approach to promote social inclusion in practice, calling for further research on this.